TARAS SHEVCHENKO IN VASYL STEFANYK’S PUBLICISM ("Read Shevchenko, and you will meet all expression, history and soul of the Ukrainian people there") - Pakhomov, V. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Vasyl Stefanyk’s discourse about the role of Taras Shevchenko in maintenance and formation of the Ukrainian people is considered in the article. The study is undertaken on the basis of Pokuttia short-story writer’s publicism.